Theoretical approaches to the economic structurization of a construction enterprise - YAKYMCHUK , Taras (Ways to Improve Construction Efficiency, 2025)
The economic structurization of a construction enterprise is a fundamental process that determines its operational efficiency, stability, and ability to adapt within a changing market environment. It encompasses the formation of a rational organizational and functional model, the optimization of the resource base, financial flows, and management processes. In its classical interpretation, structurization is viewed as the organization of all economic elements of an enterprise in accordance with the principles of efficiency and sustainable development. Under modern conditions, this process acquires a dynamic nature, taking into account digitalization, management automation, and the need for rapid response to external challenges. A construction enterprise functions as a complex system in which economic structurization ensures the coordination between production, financial, personnel, and technological subsystems. Its key aspects include resource-based, financial, organizational, and institutional approaches. The resource-based approach focuses on the optimal utilization of material, labor, and financial resources. The financial aspect relates to modeling capital flows, managing investments, and selecting effective sources of financing. The organizational approach defines the management structure, interaction between departments, coordination mechanisms, and the distribution of functions. The institutional approach considers the influence of legislation, industry standards, and state regulation on the economic structure of the enterprise. Modern economic structurization is oriented toward digital transformation, integrating information technologies, artificial intelligence, BIM, and ERP systems into management processes. This integration allows for greater precision in planning, control, and forecasting. Of particular importance is the enterprise’s financial model, which combines internal and external resources, forming a balanced system for project support. Effective structurization contributes to improved labor productivity, reduced costs, and strengthened market competitiveness. Thus, theoretical approaches to the economic structurization of construction enterprises are based on a synthesis of classical economic principles and modern digital solutions aimed at ensuring sustainable development, management efficiency, and adaptability to economic change.